Integrating Islamic Values and Local Wisdom into Science Education: Enhancing Character Development in Higher Education - Arizona, Kurniawan; Rokhmat, Joni; Ramdani, Agus; Gunawan, Gunawan; Sukarso, AA. (Ulumuna, 2025)
Education plays a pivotal role in shaping intellectual and moral character, particularly in addressing the challenges of globalization and technological advancement. In Indonesia, integrating Islamic values and local wisdom into education is essential to nurturing students with strong character and cultural awareness. This study aims to analyze the integration of Islamic values and local wisdom in science courses at higher education institutions in Lombok, and their influence on character development among prospective educators. Using a quantitative approach, data were collected from 505 first-semester students through a Likert-scale questionnaire. Statistical analysis revealed high construct validity and reliability, with Composite Reliability values exceeding 0.7 and AVE values above 0.5. The findings indicate that the integration of Islamic values and local wisdom significantly influences character development, supported by strong model predictive power (R² = 0.782 for X3; R² = 0.777 for Y). The novelty of this research lies in its interdisciplinary framework that integrates Islamic norms and cultural heritage into science education, challenging traditional views of science as value-neutral. The study recommends systematically incorporating these values into science curricula and conducting longitudinal studies to assess their long-term impact on students’ character formation and academic competencies.